Improvement of uncorrected visual acuity and contrast sensitivity with perceptual learning and transcranial random noise stimulation in individuals with mild myopia - Camilleri, Rebecca; Pavan, Andrea; Ghin, Filippo; Battaglini, Luca; Campana, Gianluca (Frontiers in Psychology, 2014)
Perceptual learning has been shown to produce an improvement of visual acuity (VA) and contrast sensitivity (CS) both in subjects with amblyopia and refractive defects such as myopia or presbyopia. Transcranial random noise stimulation (tRNS) has proven to be efficacious in accelerating neural plasticity and boosting perceptual learning in healthy participants. In this study we investigated whether a short behavioural training regime using a contrast detection task combined with online tRNS was as effective in improving visual functions in participants with mild myopia compared to a two-month behavioural training regime without tRNS (Camilleri et al., 2014). After two weeks of perceptual training in combination with tRNS, participants showed an improvement of 0.15 LogMAR in uncorrected VA (UCVA) that was comparable with that obtained after eight weeks of training with no tRNS, and an improvement in uncorrected CS (UCCS) at various spatial frequencies (whereas no UCCS improvement was seen after eight weeks of training with no tRNS). On the other hand, a control group that trained for two weeks without stimulation did not show any significant UCVA or UCCS improvement. These results suggest that the combination of behavioural and neuromodulatory techniques can be fast and efficacious in improving sight in individuals with mild myopia.